An inertial delay observer-based sliding mode control for active suspension systems. (February 2016) - Gupta, Sunny; Ginoya, Divyesh; Shendge, P D; Phadke, Shrivijay B
In this paper, an active suspension system based on an inertial delay observer combined with sliding mode control is proposed for a quarter-car model. The inertial delay observer estimates the states and the uncertainties and disturbances of a system simultaneously. It is an extension of the inertial delay control which estimates the uncertainties of a system but needs the measurement of all states. The proposed scheme needs only the sprung mass position sensor for its implementation. The overall stability of the system is proved. The scheme is validated by simulation and by experimentation on a laboratory set-up. The results obtained with the proposed scheme are compared with those obtained with a passive suspension scheme, an linear quadratic Gaussian observer-based scheme and an inertial delay control-based scheme.